2006
DOI: 10.5194/acp-6-3407-2006
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition of boundary layer aerosol over the Atlantic Ocean and at an Antarctic site

Abstract: Abstract. Aerosol chemical composition was measured over the Atlantic Ocean in November-December 1999 and at the Finnish Antarctic research station Aboa in January 2000. The concentrations of all anthropogenic aerosol compounds decreased clearly from north to south. An anthropogenic influence was still evident in the middle of the tropical South Atlantic, background values were reached south of Cape Town. Chemical mass apportionment was calculated for high volume filter samples (D p <3µm). North of the equator… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
62
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(69 citation statements)
references
References 52 publications
(69 reference statements)
5
62
0
Order By: Relevance
“…Also the studies of Legrand et al ( , 1999 provided R NS with typical values for inner Antarctica in the range of 0.1 and for costal snow of about 0.3. Several studies on marine aerosol agree on a ratio on the order of 0.3 for aerosols transported in an air parcel originating from the remote Southern ocean (O'Dowd et al, 1997;Norman et al, 2003;Norman and Leck, 2005;Virkkula et al, 2006;Ooki et al, 2007). Note that measured R NS in the SO region is always far from complete neutralization of sulfate aerosol; accordingly, the availability of acidic sulfate aerosol does not stoichiometrically limit the atmospheric NH 4 þ concentration.…”
Section: The Molar Nh 4 D /Nssso 4 2l Ratiomentioning
confidence: 80%
See 1 more Smart Citation
“…Also the studies of Legrand et al ( , 1999 provided R NS with typical values for inner Antarctica in the range of 0.1 and for costal snow of about 0.3. Several studies on marine aerosol agree on a ratio on the order of 0.3 for aerosols transported in an air parcel originating from the remote Southern ocean (O'Dowd et al, 1997;Norman et al, 2003;Norman and Leck, 2005;Virkkula et al, 2006;Ooki et al, 2007). Note that measured R NS in the SO region is always far from complete neutralization of sulfate aerosol; accordingly, the availability of acidic sulfate aerosol does not stoichiometrically limit the atmospheric NH 4 þ concentration.…”
Section: The Molar Nh 4 D /Nssso 4 2l Ratiomentioning
confidence: 80%
“…R NS values were summarized from references in this publication (e.g. Silvente and Legrand, 1993;Norman et al, 2003;Virkkula et al, 2006) and from our own records. …”
Section: The Molar Nh 4 D /Nssso 4 2l Ratiomentioning
confidence: 99%
“…Asmi et al, 2010;Zieger et al, 2010). In Antarctica, the sea salt fraction of the total aerosol is dominant especially at the coastal sites with mass concentrations extending from some hundreds of ng m −3 up to several μg m −3 and further increasing towards the Southern Ocean (Artaxo and Rabello, 1992;Wagenbach et al, 1998;Virkkula et al, 2006;Weller and Lampert, 2008a;Teinilä et al, 2014). Fresh sea salt is dominated by the coarse mode aerosol particles while aerosol ageing during long-range transport increases the concentrations in the sub-micron range (Teinilä et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…1) The majority of Antarctic boundary layer <1 µm particles in summer compose most likely of sulphates of marine origin (Bigg et al, 1984;Gras, 1983;Ito, 1989;O'Dowd et al, 1997;Shaw, 1988) possibly together with some organics (Kawamura et al, 1996;Virkkula et al, 2006c). If the decreased hygroscopicity is due to the vicinity of the particle source (ocean) this could refer to the aging effect of the aerosol particles containing organics (Buchholz et al, 2009).…”
Section: Hygroscopic Growth Factorsmentioning
confidence: 99%
“…Oceanic dimethyl sulphide (DMS) can be a source of sulphur dioxide in Antarctica, while the ocean can also be a source of both primary and secondary organics (Gantt et al, 2009;Gershey, 1983;O'Dowd et al, 2004;Spracklen et al, 2008). Kawamura et al (1996) and Virkkula et al (2006c) have observed organic carbon in aerosols in Antarctica. This gives a reason to presume a contribution of organics to particle chemistry in addition to the sulphate species.…”
Section: Introductionmentioning
confidence: 99%